The Antibiotic Sensitivity Test Comparison of Erythromycin and Ciprofloxacin Against Pseudomonas sp. Bacteria in Diabetic Foot Ulcers: Perbandingan Uji Sensitivitas Antibiotik Erythromycin dan Ciprofloxacin Terhadap Bakteri Pseudomonas sp. Pada Ulkus Kaki Diabetikum - Agustina, Novia; Purnadianti.,S.St.,M.Si, Mely; Prasetyani Putri, Mardiana; Prodyantasari4, Arshy; Ngalimatul Hikmah, Rizza (Fakultas Sains, Teknologi, dan Analsisi Institut ilmu Kesehatan Bhakti Wiyata, 2025)
Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia due to abnormal insulin secretion and function. One of the complications of diabetes mellitus is peripheral neuropathy, which can lead to diabetic ulcers. Diabetic ulcers can be caused by bacterial infections, specifically from Pseudomonas sp. Antibiotic therapy for diabetic ulcers, particularly those resulting from Pseudomonas sp. infections, has frequently encountered resistance. Therefore, it is necessary to test the sensitivity of Pseudomonas sp. bacteria to the antibiotics used for treatment. This study aims to determine the sensitivity of Pseudomonas sp. from the ulcers of DM patients to the antibiotics erythromycin and ciprofloxacin. Pseudomonas bacteria were isolated from ulcer specimens using cetrimide media, followed by a sensitivity test using the diffusion method on Mueller Hinton Agar medium at 37°C for 24 hours. The research data were analyzed using the comparative Mann-Whitney statistical test. The results showed that Pseudomonas sp. was sensitive to erythromycin by 21% and to ciprofloxacin by 29%, while resistance was 79% for erythromycin and 71% for ciprofloxacin. The statistical results indicated no significant difference between the antibiotics erythromycin and ciprofloxacin (Asymp. Sig. value 0.668). The findings of this study can provide information on the phenomenon of Pseudomonas sp. resistance to erythromycin and ciprofloxacin, offering a basis for evaluating future treatment therapies with further testing. Keywords: Pseudomonas sp, Ulcer, Erythromycin, Ciprofloxacin